2009
DOI: 10.1177/1077546309106522
|View full text |Cite
|
Sign up to set email alerts
|

Stability Analysis of a Flexible Spinning and Precessing Rotor with Non-symmetric Shaft

Abstract: The present work deals with stability analysis of a spinning non-symmetric shaft with a non-central disk mounted on a rotating (precessing) base, where the spin axis and the precession axis intersect at right angles. The nutation speed is zero and the spin and precession speeds are considered to be uniform. The motion of the rotor is such that it undergoes small elastic deformation superposed on rigid body rotation. The shaft-disk system is assumed to be axially and torsionally stiff. A four-degree- of-freedom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…There will be slide movement between the two components at the contact surface (Ghosh et al, 2010;Chen et al, 2012), which can be given by…”
Section: Dynamic Model Of Vehicle Shimmy System With Clearance In Steering Linkage Mechanismmentioning
confidence: 99%
“…There will be slide movement between the two components at the contact surface (Ghosh et al, 2010;Chen et al, 2012), which can be given by…”
Section: Dynamic Model Of Vehicle Shimmy System With Clearance In Steering Linkage Mechanismmentioning
confidence: 99%
“…Xiao et al (2005) demonstrated the effect of simultaneous dynamic softening and stiffening in a rotating beam with a tip mass. Ghosh et al (2010) analyzed a spinning and precessing rotor using a four-d.f. rotor model, where the shaft was assumed to be mass-less.…”
Section: Introductionmentioning
confidence: 99%